A systematic review of impulse control disorders in Parkinson's disease. - Callesen, M; Scheel-Krüger, J; Kringelbach, M; Møller, A (2013)
Throughout the past decade it has been recognized that dopaminergic medication administered to remedy motor symptoms in Parkinson's disease is associated with an enhanced risk for impulse control disorders and related compulsive behaviors such as hobbyism, punding, and the dopamine dysregulation syndrome. These complications are relatively frequent, affecting 6-15.5% of patients, and they most often appear, or worsen, after initiation of dopaminergic therapy or dosage increase. Recently, impulse control disorders have also been associated with subthalamic nucleus deep brain stimulation. Here we present a systematic overview of literature published between 2000 and January 2013 reporting impulse control disorders in Parkinson's disease. We consider prevalence rates and discuss the functional neuroanatomy, the impact of dopamine-serotonin interactions, and the cognitive symptomatology associated with impulse control disorders in Parkinson's disease. Finally, perspectives for future research and management of impulse control disorders in Parkinson's disease are discussed.